2019
DOI: 10.1177/2047487319850717
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of posttraumatic stress disorder and prescription opioid use on risk of cardiovascular disease

Abstract: Aim Prescription opioid analgesic use (OAU) is associated with increased risk of cardiovascular disease (CVD). OAU is more common in patients with than without posttraumatic stress disorder (PTSD), and PTSD is associated with higher CVD risk. We determined whether PTSD and OAU have an additive or multiplicative association with incident CVD. Methods and results Veterans Health Affairs patient medical record data from 2008 to 2015 was used to identify 2861 patients 30–70 years of age, free of cancer, CVD and OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Although the exact underlying mechanisms for the increased risk of MACCEs in opium-consuming patients remain to be elucidated, multiple mechanisms have been suggested for the increased risk of CVD and cardiovascular events in opium consumers. 10,15 It is well known that inflammation and oxidative stress play a pivotal role in coronary atherosclerosis and also the susceptibility of existing atheromatous plaques to acute events. 16 Multiple studies have reported that opium could induce oxidative stress and inflammation by generating proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact underlying mechanisms for the increased risk of MACCEs in opium-consuming patients remain to be elucidated, multiple mechanisms have been suggested for the increased risk of CVD and cardiovascular events in opium consumers. 10,15 It is well known that inflammation and oxidative stress play a pivotal role in coronary atherosclerosis and also the susceptibility of existing atheromatous plaques to acute events. 16 Multiple studies have reported that opium could induce oxidative stress and inflammation by generating proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown conflicting results due to the methodology and mostly the profound effect of confounding risk factors. [2][3][4][5][6][7] Fortunately in the present study the results are robust even after adjusting for major parameters such as age, smoking, glycaemic, lipid and blood pressure status. In a recent meta-analysis, incorporating the results of 41 well-designed and performed studies showed the link of coronary artery disease with opium use, whereas there was no direct link to inhospital mortality.…”
mentioning
confidence: 69%
“…Historically there was the erroneous notion that there are beneficial health effects related to opium use but emerging data are towards the other direction. [2][3][4][5] In the present study, the authors used a registry database of 28,691 patients who underwent the procedure from 2007 to 2016, covering almost a decade of surgical practice. 1 It was revealed that persistent opium consumption after CABG not only did not ameliorate the overall outcome but it was associated with 28% increased risk of 5-year mortality compared with never opium consumers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, multiple clinical and animal evidence has clarified that opium consumption not only does not confer a beneficial effect in improving glycaemic control and lipid profile and preventing CVD, but also it may aggravate metabolic disturbances and increase the risk of CVD, especially in patients with post-traumatic stress disorder. 19 However, very little is known about the effect of persistent opium consumption after surgery on the outcomes after coronary artery bypass grafting (CABG). In the present issue of the journal, authors using a registry database of 28,691 patients who underwent CABG revealed that persistent opium consumption after CABG not only did not ameliorate the overall outcome but it was associated with a 28% increased risk of 5-year mortality compared with never opium consumers.…”
Section: Ominous Effect Of Persistent Opium Consumption On the Long-tmentioning
confidence: 99%